Tenants satisfaction towards the facilities provided by Technology Park Malaysia / Siti Ainun Mardiah Jamaludin - Jamaludin, Siti Ainun Mardiah (Faculty of Business and Management, 2008)
Technology Park Malaysia (TPM), was established in 1988. It was given the status of a company under the Companies Act, and had for its objectives the commercialization of local Research and Development output and the development of indigenous technology. Other technopoles are the Johor Technology Park, the Technovation Park and the Kulim High Technology Park. All of these are property based developments that seek to attract high-technology firms by providing advanced infrastructure, a pool of technology specialists, Rand D facilities, business management expertise and venture capital within the confines of a single compound. Technology parks in Malaysia promote interaction between academia and industry, encourage the development of knowledge-based industries and stimulate job creation. As companies, these parks are also supposed to earn profits, providing a return on investment for their sponsors. They focus on programmes designed to stimulate innovation and sustain the development of novel products based on Rand D conducted in local institutions and the commercialization of those products. Technology Park Malaysia also has to provide their tenant with good services to ensure it can be a leader in incubator operator in Malaysia. This is crucial to the company to achieve the customer satisfaction and maintain the customer loyalty.